Metode Edukasi Aktif melalui Permainan Sendi Temporomandibular untuk Meningkatkan Pengetahuan Masyarakat Terkait Gangguan Sendi Rahang - Amirah Maritsa; Zahrawi Astrie Ahkam; Aisyah AR; Hasrini Hasrini; Zulkarnain Zulkarnain (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2022)
Background: This TMJ problem or jaw joint disorder is classified as an emergency, so treatment must be done immediately. The causes of this jaw joint problem are multifactorial. Generally divided into two, namely structural disorders and functional disorders. Functional disorders arise due to deviant function due to abnormalities in the position or function of the teeth and chewing muscles. Treatment, when someone has TMJ problems, is usually a reduction action that is carried out directly by a doctor. This cannot be done by ordinary people. However, sometimes people self-diagnose and resort to invalid sources which can actually lead to more serious problems.Method : The educational method is carried out by active counseling and discussions given to the people of Margasari Village. Then, the community was asked to fill out a questionnaire to assess the effectiveness of delivering material about this TMJ. Result: People who have filled out the questionnaire were found to have a significant difference between before and after being given the material. People become more aware of the material and are expected to be able to apply it in everyday life. Conclusion: There is a significant difference between before and after being given TMJ games